Editorial note - Krzanowski, Roman (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2022)
This special edition of Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce or ZFN) focuses on concepts of information and computing. On reading this issue, you may be surprised by the absence of traditional perspectives and themes that one would usually expect from such collections, but this apparent oversight is deliberate. The eight papers collected in this special edition of ZFN bring together perspectives that aim to inspire readers rather than confirm concepts that have already been researched. The main motivation behind this collection is a desire to explore the philosophical dimensions of computing and information sciences. Thus, for anyone looking for new ideas related to the philosophy of computing and information and wondering what is on the horizon, this special edition of ZFN may be the place to start.
Keywords: information; computing; Philosophical Problems in Science; ZFN